Unveiling the Linguistic Landscape of Gamers: Insights from Online Gaming Communication and Its Implication in English Materials - Igo Rizky Nur Pratama; Gusti Nur Hafifah; Jepri Ali Saiful; Sofi Yunianti (Tell : Teaching of English Language and Literature Journal, 2024)
This study investigates the online gamers' language features and their implication in vocational high school English material. A qualitative study is conducted and three aspects of language register theory including field, tenor, and lexical resources are explored. The scope, context, and situation of the online gaming interaction (Valorant and Player's Unknown Battleground) are also analyzed. The interaction among gamers happened in different types of fields and tenor depends on their roles and context in online games. The lexical resources data found that gamers dominantly used noun words beside other language features. This study recommends teachers leverage the related online games' vocabularies into their English teaching materials to encourage students learning. Further study needs to explore the influence of online gaming on students' English achievement.